'CHOICE THINGS OF VALUE': THE MYSTERIOUS GENESIS AND CHARACTER OF THE VI CONCERTOS IN SEVEN PARTS ATTRIBUTED TO ALESSANDRO SCARLATTI. (17th February 2015) - HALTON, ROSALIND; TALBOT, MICHAEL
ABSTRACT The VI Concertos in Seven Parts published by Benjamin Cooke under Alessandro Scarlatti's name in 1740 have long been suspected of being either arrangements or works by a different composer. Close study of the sources, some of which have only recently come to light, shows them to be arrangements of sonate a quattro, four composed by Alessandro Scarlatti and two by his younger brother Francesco. The unacknowledged compiler and arranger of the set was almost certainly Charles Avison, who in addition made a significant compositional intervention. The publication of the concertos formed part of a pioneering strategy on Cooke's part whereby he acquired, and under the protection of a royal privilege engraved, significant works in manuscript owned (but not composed) by individual musicians within his circle. Among the latter was John Christopher Pepusch, whose role in the first publication of Domenico Scarlatti's sonatas k31–42 is described for the first time.